UJI AKTIVITAS ANTIBAKTERI NANOPARTIKEL EKSTRAK ETANOL DAUN MATOA (Pometia pinnata J.R. Forst & G. Forst) TERHADAP BAKTERI Escherichia coli - Siregar, Huzeila Nisa; Rahayu, Yayuk Putri; Nasution, Haris Munandar; Nasution, M Pandapotan (Jurnal Riset Kefarmasian Indonesia, 2023)
Escherichia coli was one of the bacteria that causes diarrhea. Matoa leaves (Pometia pinnata J.R. Forst & G. Forst) ) is a plant from the Sapindaceae family and is known to have antibacterial compounds. This study aims to make ethanol extract of matoa leaves into extract nanoparticles and to determine the antibacterial activity of ethanol extract nanoparticles better than ethanol extract of matoa leaves against E. coli bacteria. This research was conducted experimentally with free variables, namely the concentration of matoa leaf ethanol extract (KEDM 25%; KEDM 50%; and KEDM 75%), and the nanoparticle concentration of matoa leaf ethanol extract (KNDM 2.5%; KNDM 5%; and KNDM 7.5%). The bound variable was the antibacterial activity of ethanol extract and nanoparticles of ethanol extract of matoa leaves against E. coli bacteria. Nanoparticle manufacturing uses the ionic glassing method with chitosan 0.1% and Na-TPP 0.1% (1:1). The nanoparticle size characterization of the extract used a Particle Size Analyzer (PSA). Antibacterial activity test using the diffusion method of Kirby Bauer's agar. The result of the characterization of the extract nanoparticles obtained a size of 324.97 nm. The value of the antibacterial Zone Of Inhibition (ZOI) of matoa leaf ethanol extract was 13.9 mm (KEDM 25%); 14.6 mm (KEDM 50%); and 18 mm (KEDM 75%). The antibacterial ZOI value of the ethanol extract nanoparticles was 6.6 mm (KNDM 2.5%); 7.2 mm (KNDM 5%); and 7.7 mm (KNDM 7.5%). The conclusion of this research was that matoa leaf ethanol extract can be used as an extract nanoparticle, where with a concentration of 2.5% extract nanoparticles already has antibacterial activity capability which is equivalent to half the dose of 25% ethanol extract concentration of matoa leaves, so it can be said that the extract nanoparticle preparation can reduce the dose of a drug by up to half the dose, even though it is in the resistant category compared to Tetracycline 30 μg.